Levantamento das populações de mamíferos e aves em um fragmento de caatinga no alto sertão sergipano - Freitas, Evellyn Borges de (2010)
The main aim of the present study was to advance our knowledge of the biodiversity of the Caatinga biome, the only exclusively Brazilian ecoregion, which suffers constant degradation. The study area, in the municipality of Porto da Folha, Sergipe, appears to be typical of the region, with evidence of habitat degradation and hunting pressure, factors which affect local populations of fauna and flora directly. Line transect population surveys were conducted in July, August, and December, 2009, with a total of 132.9 km walked on four trails representing the main area of the fragment. The results of these surveys provided reliable density estimates for only two species Callithrix jacchus (168.7 individuals per km²) and Kerodon rupestris (116.7 inds./km²) whereas only two sightings of the target species (Callicebus barbarabrownae) were collected. The presence of other mammals, such as the Virginia opossum (Didelphis albiventris) and the raccoon (Procyon cancrivorous) was recorded from tracks and other indirect evidence. Given the paucity of records for the target species, population parameters were estimated using playback survey methods, based on the broadcasting of the species vocalizations through a megaphone, in order to provoke a response from the animals, which reveals their position in the forest and permits the mapping of group locations through triangulation. Playback surveys were conducted between September and November, 2009. The mapped locations were analyzed in order to define the portion of the fragment occupied by the titi monkeys, and identify habitat preferences. Two resident groups were identified, in addition to the presence of at least one solitary animal. With a total of 57 records, the playback method proved far more efficient than the traditional line transect procedure for the surveying of the Callicebus population, and should be the method of choice for surveys, especially in small fragments. During complementary observations, a total of 66 bird species were recorded at the site in July, August and November, 2009. Most of the species were either insectivores (36.6%), omnivores (22.7%) or granivores (16.7%), and the largest number of species was recorded in anthropogenic habitats. In addition to providing the first detailed data on population parameters and habitat preferences in Callicebus barbarabrownae, the study emphasizes the value of playback procedures for the surveying of titi populations.